Implementation of Charity Box Security System based on Internet of Things (IoT) using Sensor and Notifications - Atmiasri; Solikin, Akhmad; Puncak Pujiputra, Anggarjuna (Universitas PGRI Adi Buana Surabaya, 2025)
Mosques are places of worship for Muslims. With a large number of mosques, the problems that arise are also diverse, for example the AL Akbar Surabaya mosque has 2 thefts per year. The form of breaking into the charity box was in the form of the destruction of the padlock hinge made of iron plates in the outer courtyard of the mosque. This is a problem for mosque managers. The purpose of this research is to create a security system for the charity box of the Al Akbar National Mosque that can be controlled remotely using the Internet of Things (IoT). This system will ensure the safety of the charity box and prevent the possibility of theft or manipulation of the money contained in it. This security system uses motion sensors as an indicator of suspicious activity around the charity box. When the vibration sensor detects vibration, the system will activate the Buzzer and the ESP32 CAM camera takes pictures to be further processed using a face detection algorithm and the results are sent in the form of a notification to the mosque manager who is connected to the internet network, so that it can take photos that can be accessed in real-time by security control. To control this security system, a mobile application will be built that can be accessed by mosque administrators. Overall, this design will provide a higher level of security for the Al Akbar National Mosque charity box. With a security system that can be accessed and controlled remotely through IoT. The mosque management can quickly respond and take action in unsafe situations.